Comparison of echocardiographic and cardiac magnetic resonance imaging measurements of systolic function during breast cancer therapy - Huynh, Judith; Malmgren, Andreas; Kraen, Morten; Trägårdh, Elin ; 0000-0002-7116-303X; Dencker, Magnus (BMC Cardiovascular Disorders, 2025)
Background: To compare echocardiographic and cardiac magnetic resonance imaging (CMR) measurements of global longitudinal strain (GLS) and global mitral annular plane displacement in women with breast cancer undergoing chemotherapy. The study focused on assessing the mitral annular plane systolic excursion (MAPSE) in echocardiography (ECHO) and atrioventricular plane displacement (AVPD) in CMR as parameters for global mitral annular plane displacement. Material and method: Consecutive breast cancer patients (n = 16) were evaluated with ECHO and CMR before, during and after chemotherapy. Echocardiographic GLS was analyzed using two different software programs (TomTec and QLab). Non-parametric Wilcoxon’s signed-rank test, Bland-Altman plots and Friedman’s test were used for the statistical analyses. A statistical significance level of all analyses was set at a p-value < 0.05. The study was approved by National Ethics Review Board in Sweden (DNR 2019–04588). Results: No significant differences were found in GLS at baseline between ECHO (median: QLab − 20.4% and TomTec − 22.0%) and CMR (median: -19.5%) (ECHO(QLab) vs. CMR p = 0.733 and ECHO(TomTec) vs. CMR p = 0.093). After chemotherapy significant reductions in GLS were measured with ECHO(TomTec) (median: -20.1, p = 0.035) and CMR (median GLS: -17.4%, p = 0.004). At baseline ECHO-MAPSE (median: 16.8 mm) and CMR-AVPD (median: 14.0 mm) differed significantly (p = 0.015). However, no significant reduction of MAPSE (median: 15.5 mm) or AVPD (median: 13.8 mm) were detected after chemotherapy (p = 0.076 respective p = 0.706). Though ECHO-MAPSE showed a tendency to decrease after chemotherapy, CMR-AVPD did not. Conclusion: ECHO(TomTec)-GLS is as compatible to detect early signs of cardiotoxicity as CMR. ECHO-MAPSE could be more sensitive than CMR-AVPD to detect subtle changes during chemotherapy.
Keywords: Cardiotoxicity; Global longitudinal strain; Mitral annular plane systolic excursion